MicroRNAs play an essential role in autophagy regulation in various disease phenotypes. (16th August 2019) - Zhao, Yunyi; Wang, Ze; Zhang, Wenhui; Zhang, Linbo
Abstract: Autophagy is a highly conserved catabolic process and fundamental biological process in eukaryotic cells. It recycles intracellular components to provide nutrients during starvation and maintains quality control of organelles and proteins. In addition, autophagy is a well‐organized homeostatic cellular process that is responsible for the removal of damaged organelles and intracellular pathogens. Moreover, it also modulates the innate and adaptive immune systems. Micro ribonucleic acids (microRNAs) are a mature class of post‐transcriptional modulators that are widely expressed in tissues and organs. And, it can suppress gene expression by targeting messenger RNAs for translational repression or, at a lesser extent, degradation. Research indicates that microRNAs regulate autophagy through different pathways, playing an essential role in the treatment of various diseases. It is an important regulator of fundamental cellular processes such as proliferation, autophagy, and cell apoptosis. In this review article, we first review the current knowledge of autophagy and the function of microRNAs. Then, we summarize the mechanism of autophagy and the signaling pathways related to autophagy by citing at least the main proteins involved in the different phases of the process. Second, we introduce other members of RNA and report some examples in various pathologies. Finally, we review the current literature regarding microRNA‐based therapies for cancer, atherosclerosis, cardiac disease, tuberculosis, and viral diseases. MicroRNAs can cause autophagy upregulation or downregulation by targeting genes or affecting autophagy‐related signaling pathways. Therefore, the microRNAs have a huge potential in autophagy regulation, and it is the function as diagnostic and prognostic markers.